n → ∞ lim ( 1 ln ( 1 + n 1 ) + 2 ln ( 1 + n 2 ) + 3 ln ( 1 + n 3 ) + ⋯ + n ln 2 )
If the limit above equals to A , find ⌊ 1 0 4 A ⌋ .
Notation:
⌊
⋅
⌋
denotes the
floor function
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
The summation could be expressed as
A = n → ∞ lim k = 1 ∑ n k ln ( 1 + n k )
We could modify a little bit of the RHS and get
A = n → ∞ lim n 1 k = 1 ∑ n n k ln ( 1 + n k )
Well, this is actually the Riemann Sum representation of the integral
A = ∫ 0 1 x ln ( 1 + x ) d x
Which, at first glance, isn't computable.
Let us turn to power series for help.
Note that ln ( 1 + x ) = x − 2 x 2 + 3 x 3 − 4 x 4 + 5 x 5 . . .
ln ( 1 + x ) = x − 2 x 2 + 3 x 3 − 4 x 4 + 5 x 5 . . .
x ln ( 1 + x ) = 1 − 2 x + 3 x 2 − 4 x 3 + 5 x 4 . . .
∫ 0 x x ln ( 1 + x ) = x − 4 x 2 + 9 x 3 − 1 6 x 4 + 2 5 x 5 . . .
Substituting x = 1 to the above equation, we get an infinite sum equating to A .
Now, we know of this sum
6 π 2 = 1 + 4 1 + 9 1 + 1 6 1 + 2 5 1 + 3 6 1 + . . .
1 2 π 2 = 2 1 + 8 1 + 1 8 1 + 3 2 1 + . . .
6 π 2 − 1 2 π 2 = 1 + ( 4 1 − 2 1 ) + 9 1 + ( 1 6 1 − 8 1 ) + 2 5 1 + ( 3 6 1 − 1 8 1 ) + . . .
1 2 π 2 = 1 − 4 1 + 9 1 − 1 6 1 + 2 5 1 − 3 6 1 + . . . = A
So that's it! A = 1 2 π 2 , such that
⌊ 1 0 4 A ⌋ = 8 2 2 4